LEAD TOXICITY AND ITS AMELIORATION EFFECT BY FOLIAR APPLICATION OF HORMONE AND MICRONUTRIENTS IN VIGNA RADIATA L. WILCZEK - SANJOY SHIL SUMITA NAG, PEENAZ UBED, L.VASUDEVA REDDY, SIRAJUL ISLAM, Sk. ABDULLAH, SUDESHNA MUKHERJEE ELORA MUKHOPADHYAY, (The Bioscan, 2015)
Studies were carried out on the phytotoxicity of Lead (Pb) on some biochemical parameters like chlorophyll, protein, nucleic acid content and some enzymatic activities of Vigna radiata L. seedlings were treated with 100μm and 200μm concentration of Lead nitrate (PbNo3) as well as Copper sulphate (CuSo4) and also with 20ppm and 30ppm Indole Acetic Acid (IAA) at 21 days of sowing and carried out up to 50% flowering stage with a gap of 7 days between the foliar spraying. Lead nitrate solutions have been sprayed to study the intensity of damage and CuSo4, IAA solutions have been sprayed to minimize or overcome the heavy metal stress. Results indicated that increasing lead nitrate level (from100 μm to 200 μm) leads to several disruptions of plants which were reflected by reductions of chlorophyll (from 0.341mg to 0.312mg), protein (268.251mg to 266.032mg), DNA(from 9.033mg to 8.837mg) and RNA(from 0.859mg to 0.827mg) content. However, few enzymatic analyses such as chlorophyllase, catalase and peroxidase activities of treated samples were increasing with the increasing level of lead concentrations. Regarding detoxification, foliar spray of CuSo4 (100μm or 200 μm and IAA (20ppm or 30ppm) showed significant result to nullify the damaging effect of Pb to a great extent either by their individual treatment with Pd or by combined treatment of CuSo4 along with IAA, whereas best amelioration was obtained with Pb+ CuSo4 +IAA treatment (100μm or 200μm +30ppm+200μm). From the overall experimental observation, conclusion may be drawn that heavy metal like Pb has a positive definite harmful effect over green gram seedlings even in low concentration and these damaging effect could be minimize with the help of micronutrients and hormonal treatments.